KEGIATAN SOSIAL, BUDAYA, DAN AGAMA DALAM MENENTUKAN LABA LEMBAGA PERKREDITAN DESA (LPD) KOTA DENPASAR - Prena, Gine Das; Kustina, Ketut Tanti (E-Jurnal Akuntansi; Vol 21 No 1 (2017), 2017)
This study aimed to determine the social activities, cultural activities, religious activities conducted LPD in supporting  its profit. The study was conducted overall the population  of thirty LPD, which spread in Denpasar District East, South Denpasar, Denpasar Denpasar West and North, by spreading questioner on board LPD. Research hypothesis testing using multiple linear regression analysis. Based on the survey results revealed that the social,cultural, and religious activities significantly influence the success of LPD. In simultant, social, cultural, religious, activities are participate to the success of LPD in the city of Denpasar. The implication of this research is social, cultural, religious proven the success of the credit institutions participating in Denpasar village, then the village credit institutions are expected to continue to increase the empowerment of its profits to social activities, culture, and religion held in where LPD operate.
Keywords: Social activities, cultural activities, religious activities, LPD profit